Influence of the glycerol content and temperature on the rheology of native and acetylated starches during and after gelatinization - Moran, Juan Ignacio (2011)
Native potato starch was acetylated and characterized. The influence of this chemical modification on different properties of the starch was studied. The characterization included the molecular weight, thermal properties, crystallinity, amylose content, swelling behavior, and pasting and rheological properties. The chemical modification induced small changes in the crystallinity of the starch and a reduction in the gelatinization heat and in the range of temperatures at which it took place. The amylose content was determined for acetylated and native potato starches. The swelling of native granules was higher than the swelling of acetylated potato starch. Regarding pasting behavior, the native and acetylated starches responded in similar ways to changes in the temperature and glycerol content. Finally, the acetylated starch was less pseudoplastic than the native starch.